Trip and mode choice decisions to out-patient health care facilities: A longitudinal analysis - Patrick McCarthy (Journal of Management Science and Engineering, 2022)
This paper analyzes the impact of health indicators on an individual's trip and mode choices to out-patient care facilities. The study's focus is an out-patient trip to a health care facility, and the source of data is the China Health and Retirement Longitudinal Study (CHARLS) for 2011, 2013 and 2015. Based on a random utility framework, the study finds that making a trip to treat an illness or for a check-up increases the likelihood of an out-patient trip by 52 and 31 probability points, respectively. Out-patient visits for which insurance is not relevant, when the individual pays most of the out-of-pocket costs and when the facility is a public facility are also important factors. Diagnosed and other personal health factors have some but much more modest effects on one's trip choice. The analysis also identifies differential modal impacts of health indicators. A series of robustness tests generally confirm the results and identify areas for further research. Including a no-trip option, the biannual survey and infrequent out-patient trip-making mitigate endogeneity concerns. The analysis has broad health policy and transportation implications for an ageing population whose share is increasing.